THE EXTRAORDINARY COMMISSION TO COMBAT COUNTER-REVOLUTION IN THE STAVROPOL AND TEREK REGIONS IN THE 1920-S - T. Bulygina; V. Romanov (Гуманитарные и юридические исследования)
The article is devoted to features of functioning of VChK in the south of Russia after the end of the Civil war.